+0  
 
0
271
4
avatar+10 

Hi! How do you simplify (4x^6y^5)^2? Im doing an online summer course in math

Mozziee  Jul 27, 2014

Best Answer 

 #1
avatar+91489 
+8

$$(4x^6y^5)^2$$

There are rules for this but it is probably better if you just understand so I will try to explain.

$$(4x^6y^5)^2\\\\
=4x^6y^5 \times 4x^6y^5\\\\
=4\times x^6 \times y^5\times 4\times x^6 \times y^5\\\\
=4\times 4\times x^6 \times x^6\times y^5\times y^5 \\\\
=16x^{12} y^{10} \\\\
\mbox{Now for the short cut method}\\
(4 x^6y^5)^2 = 4^2x^{6*2}y^{5*2} = 16x^{12}y^{10}$$

 

If you do not understand then please make another post on THIS thread.  Thank you.

Melody  Jul 27, 2014
Sort: 

4+0 Answers

 #1
avatar+91489 
+8
Best Answer

$$(4x^6y^5)^2$$

There are rules for this but it is probably better if you just understand so I will try to explain.

$$(4x^6y^5)^2\\\\
=4x^6y^5 \times 4x^6y^5\\\\
=4\times x^6 \times y^5\times 4\times x^6 \times y^5\\\\
=4\times 4\times x^6 \times x^6\times y^5\times y^5 \\\\
=16x^{12} y^{10} \\\\
\mbox{Now for the short cut method}\\
(4 x^6y^5)^2 = 4^2x^{6*2}y^{5*2} = 16x^{12}y^{10}$$

 

If you do not understand then please make another post on THIS thread.  Thank you.

Melody  Jul 27, 2014
 #2
avatar+10 
0

Thanks a lot! I will take a look :)

 

Edit: I understand perfectly now!

Mozziee  Jul 27, 2014
 #3
avatar+752 
0

This is a very different question.

It is:

(((4x-)^6y)^5)^2)

=((4x)^6y)^10

=(4x)^60y

This is the answer for ur question

Sasini  Jul 27, 2014
 #4
avatar+91489 
0

(((4x-)^6y)^5)^2)

Puttin a minus sign there does not make sense Sasini.  

Melody  Jul 27, 2014

7 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details